Validation and Normative Data of the Spanish Version of the Rey Auditory Verbal Learning Test and Associated Long-Term Forgetting Measures in Middle-Aged Adults - Alviarez-Schulze, Vanessa; Cattaneo, Gabriele; Pachón-García, Catherine; Solana-Sánchez, Javier; Tormos, Josep M.; Pascual-Leone, Alvaro; Bartrés-Faz, David (Frontiers in Aging Neuroscience, 2022)
Rey Auditory Verbal Learning Test (RAVLT) is an episodic memory helpful measure to detect changes associated with abnormal aging. There is a lack of RAVLT validation and normalization studies in Spain. The aim was to determine its psychometric properties and explore long-term forgetting (LTF) performance through 1-week delayed recall under three different modes of administration. The RAVLT was administered to 602 cognitively healthy volunteers aged between 41 and 65 years, of whom 251 completed the LTF assessment. Findings reveal a factorial structure of four components, with satisfactory goodness of fit, and adequate convergent and divergent validity. We also demonstrated the differential effect of three methodologies used in LTF assessment, supporting that test expectancy positively influence long-term storage. Finally, normative data was generated, according to age, sex and education. The test, including the LTF measure, is a promising tool to estimate memory in middle-aged adults and develop predictive brain aging models.